Labour stress control of teachers through emotional training - Salmurri Trinxet, Ferran; Skoknic Cvitanic, Vania (Revista de Psicología, 2003)
In this work, we present an intervention package applied a sample of school teachers, to train these workers in emotional strategies. A set of cognitive, behavioral and emotional skills was used to control clinical symptomathology and stress control. The results obtained, suggest this psychological intervention work it, because we observed a decline of symptoms and reduction work days lost, after intervention program.